Examining the Effects of Tourism Activities on the Livelihood of Communities Living in and Around Queen Elizabeth National Park. - Mwije, Eziryerl (Kabale University, 2024)
This study, titled "Examining the Effects of Tourism Activities on the Livelihood of Communities Living In and Around Queen Elizabeth National Park," investigates the impact of tourism on the socio-economic conditions of local communities. Utilizing a cross-sectional study design, the research involved 133 respondents, including government authorities, social and economic developers, elected politicians, and local community members. Data was collected through interviews, questionnaires, and observation, integrating both quantitative and qualitative analyses to provide a comprehensive understanding of the subject findings reveal that while tourism significantly contributes to the local economy by creating jobs and generating income, it also presents challenges such as seasonal employment, income instability, and environmental degradation. The reliance on tourism as a primary income source has made local communities vulnerable to economic fluctuations, particularly during the off-season. Moreover, environmental concerns, including habitat destruction and resource depletion, have emerged as critical issues needing urgent attention. To address the challenges identified, the study proposes several key strategies: promoting the diversification of income sources through alternative livelihoods such as agriculture and small businesses to reduce dependency on tourism; implementing financial literacy programs to help communities better manage their finances, particularly during low tourist seasons; encouraging sustainable tourism practices by emphasizing environmental conservation and involving local communities in sustainability efforts to ensure long-term benefits from tourism; developing year-round tourism initiatives to provide consistent income throughout the year; strengthening community engagement by enhancing the involvement of local communities in tourism planning and decision-making; and reinvesting tourism revenue into local infrastructure and healthcare services to improve overall community well-being.